Toward a Mechanistic Understanding of Anaerobic Nitrate-Dependent Iron Oxidation: Balancing Electron Uptake and Detoxification - Carlson, Hans K.; Clark, Iain C.; Melnyk, Ryan A.; Coates, John D. (Frontiers in Microbiology, 2012)
The anaerobic oxidation of Fe(II) by subsurface microorganisms is an important part of biogeochemical cycling in the environment, but the biochemical mechanisms used to couple iron oxidation to nitrate respiration are not well understood. Based on our own work and the evidence available in the literature, we propose a mechanistic model for anaerobic nitrate dependent iron oxidation. We suggest that anaerobic iron oxidizing microorganisms likely exist along a continuum including: 1) bacteria that inadvertently oxidize Fe(II) by abiotic or biotic reactions with enzymes or chemical intermediates in their metabolic pathways (e.g. denitrification) and suffer from toxicity or energetic penalty, 2) Fe(II) tolerant bacteria that gain little or no growth benefit from iron oxidation but can manage the toxic reactions, and 3) bacteria that efficiently accept electrons from Fe(II) to gain a growth advantage while preventing or mitigating the toxic reactions. Predictions of the proposed model are highlighted and experimental approaches are discussed.